Effects of Southern Thai Traditional Massage with Warm Compression on Lactation and Breast Engorgement: A Randomized Controlled Trial - Chudanut Khoonphet; Sopen Chunuan; Sasitorn Phumdoung (Pacific Rim International Journal of Nursing Research, 2022)
Lactation problems including delayed onset of lactation, insufficient milk volume, and breast engorgement are important barriers for primiparous mothers because these lead to their early stopping of exclusive breastfeeding. Therefore, a randomized controlled trial was conducted with primiparous mothers to investigate the effects of Southern Thai traditional massage with warm compression on onset of lactation, milk volume, and breast engorgement. A minimized randomization program was used to assign the participants into either 1) Southern Thai traditional massage with warm compression group (n = 21), 2) Southern Thai traditional massage group (n = 21), or 3) control group (n = 21) who received usual care. The instruments used for data collection consisted of a Demographic Data Form, the Onset of Lactation Form, the Milk Volume Recording Form, and the Six-Point Engorgement Scale. Descriptive and inferential statistics were used to analyze the data. The results showed that the onset of lactation was significantly earlier and milk volume was significantly higher in the Southern Thai traditional massage with warm compression group than those in the Southern Thai traditional massage and control groups. Breast engorgement in the Southern Thai traditional massage with warm compression group was significantly lower than those in the Southern Thai traditional massage and control groups. Therefore, the Southern Thai traditional massage with warm compression intervention is effective in improving lactation and breast engorgement. Thus, nurses can use this intervention by teaching nurse-midwife, pregnant women, and relatives to promote the onset of lactation, increase milk volume, and prevent breast engorgement. Further testing with different groups is required before this can be extended to other population groups.